Pengaruh Lama Fermentasi Terhadap Karakteristik Minuman Probiotik Jus Pepaya (Carica papaya L.) dengan Isolat Weissella confusa. F213 - Wahyu Adi, Noval; Yusa, Ni Made; Nocianitri, Komang Ayu (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2022)
The aim of this research was to determine the effect of fermentation time on the characteristics of papaya juice probiotic with Weissella confusa. F213 and knowing the right fermentation time to produce papaya juice probiotic drink products with the best characteristics. This study used a completely randomized design (CRD) with treatment duration of fermentation consisting of 16 hours, 20 hours, 24 hours, 28 hours, 32 hours and 36 hours. Each treatment was repeated 3 times to obtain 18 experimental units. Total data of lactic acid bacteria were analyzed descriptively and other data were analyzed statistically by analysis of variance (ANOVA) and continued with Duncan multiple range test (DMRT), if there was an effect between treatments. The results showed that the fermentation time significantly affected the total acid, pH and texture scoring. Fermentation for 16 hours resulted papaya juice probiotic with the best characteristics with a total LAB of 8.08 x106cfu/ml, total sugar 15.94%, total acid 0.65%, acidity (pH) 4.64, color preferred, smell slightly liked, texture slightly liked, slightly sour taste and the overall reception a slightly liked.